Assessing the Effect of Tebucunazole on Aspergillus flavus and Fusarium verticillioides Growth in Maize Seeds in Uganda - Ritah Mutambi (Uganda Christian University, 2025)
Tebuconazole, a triazole fungicide is used for effective control of the fungal pathogens in other crops. Little information regarding the use of tebuconazole fungicide is known. Therefore, this study aims at evaluating the effect of tebuconazole on growth of A. flavus and F. verticillioides in maize seeds. Completely randomized design (CRD) with three replications was used to determine fungal growth and changes in physical traits of maize seeds and the germination rate. Data was collected on fungal growth (colonies, capping, and abnormal seeds) and seedling growth. The results showed that was a significant difference (p< 0.004) among the tebuconazole concentrations on the fungal growth, physical traits and germination rate of maize seeds. The high dose had the highest normal seeds (72.65 ± 16.14a) with the lowest number of abnormal seeds (23.47 ± 15.14c) and capping (5.13 ± 8.45ab) while Control had the lowest number normal seeds (50.57 ± 28.33c) with highest number of abnormal seeds (44.40 ± 27.57a) and capping (7.94 ± 8.04a). White fungal colonies were present in 100% of the samples across all treatments, high dose was the most effective in reducing presence of yellow, green, grey and brown fungal colonies. The highest germination percentage (96.67 ± 4.880c) was recorded in the control while the recommended dose had the lowest germination percentage (63.33 ± 9.759a). Since, the recommended dose (0.5ml) of tebuconazole effectively controlled the fungus, it is the most effective dosage for controlling of A. flavus and F. verticillioides in maize seeds.
Undergraduate